Human interface and the management of information symposium on human interface 2011, held as part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011, proceedings. Part II - Salvendy, Gavriel; Smith, Michael J. (Lecture notes in computer science, 2011)
This two-volume set LNCS 6771 and 6772 constitutes the refereed proceedings of the Symposium on Human Interface 2011, held in Orlando, FL, USA in July 2011 in the framework of the 14th International Conference on Human-Computer Interaction, HCII 2011 with 10 other thematically similar conferences. The 137 revised papers presented in the two volumes were carefully reviewed and selected from numerous submissions. The papers accepted for presentation thoroughly cover the thematic area of human interface and the management of information. The 62 papers of this second volume address the following major topics: access to information; supporting communication; supporting work, collaboration; decision-making and business; mobile and ubiquitous information; and information in aviation.